RÉGÉNÉRATION IN VITRO PAR ORGANOGENÈSE DIRECTE DE POUSSES À PARTIR DE BOUTURES DE TROIS CULTIVARS DE PATATE DOUCE (IPOMOEA BATATAS) ORIGINAIRE DU TOGO - Kodjo, Glato; Atsou, Aidam; Komi, Odah; Koffi, Tozo; M-L, Attoh-Mensah; Djidjolé, Etse Kodjo; Dzifa, Kokoutse Adzo; Aziadekey, Mawuli; Akpavi, Sêmihinva; Essozima, Aliaki; Rassimwaï, Pitekelabou (European Scientific Journal, ESJ, 2014)
The sweet potato (Ipomoea batatas), plant is difficult to conventional improvement. Technical’s methods by organogenesis remain the way to improve the material. The objective of our work is to test the potential of three local clones from cultivars of sweet potato cultivated in Togo: Damadoami, Tombolo and Nagohé in the influence of the BAP. Two clones: clone 1 Nagohé and clone 2 Tombolo are recalcitrant to be regenerated in plants during the eight weeks of culture. Both clones of Damadaomi gave a total of 798 new buds with 370 buds for clone1 and 428 for clone 2 to 192 because of cutting by cutting 96 clones. Clone 1 of Tombolo and clone 2 Nagohé produced respectively 562 and 326 buds for 96 cuttings with an average of 5,85 to 3,39 for Tombolo and Nagohe respectively. Our work has shown that some clones of sweet potato cultivars of Togo respond well to organogenesis and may be potential candidates for genetic improvement.